Twin Pati-Salam theory of flavour with a TeV scale vector leptoquark - Stephen F. King (SpringerOpen, 2021)
Abstract We propose a twin Pati-Salam (PS) theory of flavour broken to the G 4321 gauge group at high energies, then to the Standard Model at low energies, yielding a TeV scale vector leptoquark U 1 μ $$ U_1^{μ } $$ (3, 1, 2/3) which has been suggested to address the lepton universality anomalies R K ∗ $$ R_{K^{\left(* \right)}} $$ and R D ∗ $$ R_{D^{\left(* \right)}} $$ in B decays. Quark and lepton masses are mediated by vector-like fermions, with personal Higgs doublets for the second and third families, which may be replaced by a two Higgs doublet model (2HDM). The twin PS theory of flavour successfully accounts for all quark and lepton (including neutrino) masses and mixings, and predicts a dominant coupling of U 1 μ $$ U_1^{μ } $$ (3, 1, 2/3) to the third family left-handed doublets. However the predicted mass matrices, assuming natural values of the parameters, are not consistent with the single vector leptoquark solution to the R D ∗ $$ R_{D^{\left(* \right)}} $$ anomaly, given its current value.